PENGARUH DISIPLIN KERJA DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PIZZA HUT WILAYAH JAKARTA TIMUR - Rizky, Pratama; Wahjusaputri, Sintha; Wibowo, Adityo Ari (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2020)
This study aims to determine the effect between Work Discipline and Organizational Culture for Job Satisfaction. The variables used are Work Discipline and Organizational Culture as independent variables and Job Satisfaction variables as the dependent variable. The purpose of this study is to determine and analyze 1) The effect of Work Discipline on employees Job Satisfaction of Pizza Hut East Jakarta Region 2) The effect of Organizational Culture on employees Job Satisfaction of Pizza Hut East Jakarta Region 3) The effect of Work Discipline and Organizational Culture on employees Job Satisfaction of Pizza Hut East Jakarta Region